Analisis Audit Atas Beban Operasi Dalam Meningkatkan Akuntanbilitas Dan Transparansi Laporan Keuangan - Atika Tri Yudiman (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze the role of auditing operating expenses in improving the accountability and transparency of financial statements. The research method used is a qualitative approach with data collection techniques through literature study and financial document analysis. The results of the analysis show that the systematic and continuous implementation of auditing operating expenses can improve the reliability of financial information, minimize the risk of errors and fraud, and strengthen the company's internal control system. In addition, effective audits also assist management in making more accurate and responsible decisions. Thus, audits of operating expenses play a significant role in producing accountable and transparent financial reports